An Analysis of Selected Digital and Financial Indicators in the Polish Banking Sector in 2014–2018 - Cirin, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: To determine the level of selected indicators of changes in digital activity of clients relative to financial indicators achieved by the banking sector. Research Design & Methods: The article presents an integrated analysis of selected financial indicators of the Polish banking sector for 2014–2018 in comparison with selected indicators characterising the behaviour of bank customers in the digital environment. Based on the cumulative average annual growth rate (CAGR) of the phenomena under study, a high level of correlation was established and an analysis based on a linear regression model was performed. The analysis was enriched by determining the status of business financing strategies that have been implemented. This was done by using the internal rate of return model and the sustainable growth rate model. Findings: There is a strong positive correlation between selected cumulative indicators of average annual growth (CAGR) of the digital and financial spheres with the leading role of indicators of the digital sphere. During the period studied, the Polish banking sector implemented a moderately conservative financing strategy. There was a lower increase in revenues than assets, while ROE and ROA both fell. Implications / Recommendations: Further digitization of the Polish banking sector will require investment. Behaviour in the digital sphere has changed to a disproportionately greater extent than the actual financial results achieved. Moderate financing strategies are inadequate in relation to changes in selected customer behaviours in the digital sphere. The process of banks adapting to their clients’ digital attitudes and taste will require significant outlays. At the same time, margins are compressing, while revenues are growing more slowly than assets. Contribution: This integrated analysis of behavioural factors and financial results by sector (banking sector) enables linear regression-based forecasting of future selected indicators in the digital and financial spheres. It also enables the scope of the demand for external sources of financing to be forecast for these sectors.